(untitled) (Filološke pripombe, 2019)
Up to 1990 particles were generally treated from the formal aspect mainly in various grammar textbooks. As a separate group of words, viewed as a result of their syntactic behaviour and semantic function in the text, the particles have become a subject of interest ever since 1990s. For us, particles are unchangeable words with hardly any fixed syntactic position, i.e. they change their position in the sentence (as a contrast to the adverbs, prepositions and conjunctions). From the semantic point of view they are predicates, they have a broad range of mobility and can change the meaning of the sentence. They can stress any constituent part of the sentence with lexical meaning. In this paper, the Slovenian lexemes še, že, samo, le, celo and the Macedonian ones уште, веќе, само, дури (и) are the subject of our analysis. According to our definition these lexemes are in fact particles when viewed from the point of their syntactic behaviour as well as their semantic functions. In the research description of each of the Slovenian particle is given with its Macedonian equivalent and vice-versa. In the description the syntactic mobility is checked first which is followed by the semantic interpretation of their functions. Thus through the application of the confronting method we are given the possibility to process the similarities and the differences which appear in the two Slavic languages, typologically different yet showing to what extent they may come close or differentiate.